Investigation of the effects of central rectangular gap located in the adhesive layer on failure load and joint stiffness - Oz, Ozkan; Ozer, Halil; Elen, Nurhan Cevik (SPRINGER HEIDELBERG, 2022)
The purpose of this study is experimentally and numerically to reveal the effects of rectangular gap located in the middle of the adhesive layer on the failure load of the single lap joint with various adhesives. The presence of a rectangular gap in the bondline center can be considered both as an adhesive defect and, when gap limits are set correctly, it can also be considered as an adhesive saving. What is intended to be done in this study is to reveal these limits correctly. The effects of the gap length, adhesive type on the von Mises equivalent stress distribution and failure load in the recessed joints were analyzed numerically. For this purpose, four different gap lengths and three different adhesives were considered. The tensile stiffness investigations for the recessed joints were performed. In addition, the effect of the gap length on the failure load of the recessed joints with various adhesives was investigated experimentally. As a result, in the design of recessed joint, although the effect of other parameters considered was also involved, it was seen that especially the adhesive property was clearly the main design parameter.
Keywords: Recessed joint; von Mises equivalent stress; Failure load; Stiffness; SINGLE-LAP JOINT; BONDED JOINTS; STRENGTH; DEFECTS; BEHAVIOR; LENGTH; MONO; Engineering